2017
DOI: 10.3168/jds.2017-12767
|View full text |Cite
|
Sign up to set email alerts
|

Farm business and operator variables associated with bulk tank somatic cell count from dairy herds in the southeastern United States

Abstract: Mastitis is a worldwide problem in dairy cows and results in reduced milk production, the culling of cows, and other economic losses. Bulk tank somatic cell count (BTSCC) over 200,000 cells/mL often indicates underlying subclinical mastitis in dairy herds. Several preventative measures that can be implemented to help improve the incidence of mastitis exist, but surveys find these practices not fully adopted by producers. The goal of this research was to analyze the farm and operator characteristics associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 23 publications
(64 reference statements)
0
25
0
Order By: Relevance
“…Regrettably, and as we have already said, numerous studies have recorded higher levels than this. There are limited time series data regarding bulk tank SCC from Asian and African countries, nevertheless, several studies have found higher values in tropical regions of these continents than in temperate regions of North America and Europe (Kelly et al, 2009;DeLong et al, 2017;Aghamohammadi et al, 2018). Suriyasathaporn et al (2012) in Thailand and Hashemzadeh and Khalajzadeh (2014) in Iran reported bulk tank SCC > 500 000 cells/ml and about 347 000 cells/ml during 2010-12 and 2006-07 respectively.…”
Section: Heat Stress and Somatic Cell Count (Scc)mentioning
confidence: 99%
“…Regrettably, and as we have already said, numerous studies have recorded higher levels than this. There are limited time series data regarding bulk tank SCC from Asian and African countries, nevertheless, several studies have found higher values in tropical regions of these continents than in temperate regions of North America and Europe (Kelly et al, 2009;DeLong et al, 2017;Aghamohammadi et al, 2018). Suriyasathaporn et al (2012) in Thailand and Hashemzadeh and Khalajzadeh (2014) in Iran reported bulk tank SCC > 500 000 cells/ml and about 347 000 cells/ml during 2010-12 and 2006-07 respectively.…”
Section: Heat Stress and Somatic Cell Count (Scc)mentioning
confidence: 99%
“…This suggests a relationship between producers increased mastitis concerns and increased BTSCC. Jansen et al (2009) and DeLong et al (2017) observed that 48 and 65% of variation in BTSCC was explained by behaviors and attitudes towards mastitis and concern and control methods, respectively. However, Schewe et al (2015) reported that producers become concerned about BTSCC when counts exceed 300 000 cells/ml.…”
Section: Discussionmentioning
confidence: 99%
“…The research was supported by funding from the USDA-AFRI (Grant 2013-68004-20424), as part of a larger survey project (DeLong et al, 2017). Surveys were mailed to all grade A dairies (n = 1855) in Georgia, Kentucky, Mississippi, North Carolina, South Carolina, Tennessee, and Virginia between 2013and 2014, as described in DeLong et al (2017.…”
Section: Methodsmentioning
confidence: 99%
“…Some dairy extension activities are known to be valuable to farmers (Hall et al, 2019). Activities such as participatory discussion groups were associated with decreased SCC at the herd level (Dillon et al, 2016), and receiving information from an extension officer was associated with lower bulk tank SCC (Delong et al, 2017). Similarly, discussions in Danish stable schools allowed for farmers to work collectively on a problem and identify their own farm-specific goals (Vaarst et al, 2007a).…”
Section: Extension Activities In the Dairy Industrymentioning
confidence: 99%